Collected Papers of Thomas A. Heller (University of Maribor Press, 2025)
The monograph »Collected Papers of Thomas A. Heller« brings together the significant scholarly contributions of Thomas Heller, an esteemed American legal expert whose academic influence has resonated well beyond the borders of his home country. In his academic writings, Heller explored a broad spectrum of legal topics, reflecting both the depth of his expertise and the diversity of his intellectual interests. His work addressed important issues in criminal and civil procedure (such as attorney fees, remedies), topics that lie at the core of any legal system and continue to provoke scholarly debate. Particularly noteworthy are his contributions related to medical-legal issues such as medical malpractice, vaccination policies, and abortion law, mainly last analyzed through the lens of recent and landmark judicial decisions in the US. These topics are of enduring legal, ethical, and social significance. In addition, he also contributed to the field of English legal writing and composition, helping to clarify and elevate the standard of the English language.